2000
DOI: 10.1523/jneurosci.20-17-06421.2000
|View full text |Cite
|
Sign up to set email alerts
|

Passive or Active Immunization with Myelin Basic Protein Promotes Recovery from Spinal Cord Contusion

Abstract: Partial injury to the spinal cord can propagate itself, sometimes leading to paralysis attributable to degeneration of initially undamaged neurons. We demonstrated recently that autoimmune T cells directed against the CNS antigen myelin basic protein (MBP) reduce degeneration after optic nerve crush injury in rats. Here we show that not only transfer of T cells but also active immunization with MBP promotes recovery from spinal cord injury. Anesthetized adult Lewis rats subjected to spinal cord contusion at T7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
249
1
12

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(278 citation statements)
references
References 79 publications
16
249
1
12
Order By: Relevance
“…Therefore, boosting the immune responses to CNS injury under certain conditions may be more beneficial than harmful to functional regeneration (58) . Implantation of activated macrophages (86) or T-lymphocyte mediated immune activity, achieved by either adoptive transfer or active immunization (87)(88)(89)(90) , enhances recovery from spinal cord injury by conferring neuroprotection or regeneration. Although the concept of neuroprotective autoimmunity is intriguing, there is no definitive mechanism that explains its efficacy.…”
Section: Therapeutic Vaccination: Good or Bad?mentioning
confidence: 99%
“…Therefore, boosting the immune responses to CNS injury under certain conditions may be more beneficial than harmful to functional regeneration (58) . Implantation of activated macrophages (86) or T-lymphocyte mediated immune activity, achieved by either adoptive transfer or active immunization (87)(88)(89)(90) , enhances recovery from spinal cord injury by conferring neuroprotection or regeneration. Although the concept of neuroprotective autoimmunity is intriguing, there is no definitive mechanism that explains its efficacy.…”
Section: Therapeutic Vaccination: Good or Bad?mentioning
confidence: 99%
“…A decade ago, our laboratory discovered the importance of the self-reactive T cells in the repair of central nervous system (CNS) injury. 5 The protective capacity of autoimmune cells was further shown in several models of CNS pathology including mechanical injury, 5,6 Alzheimer's disease, 7 Parkinson's disease 8 and imbalances in neurotransmitter levels, 9 as well as non-CNS processes such as skin wound healing. 10 The neuroprotective immune response is a physiological response that is spontaneously evoked after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, immune neuroprotection is antigen-specific, and aimed at antigens expressed at the site of insult. 6,12,13 In addition to the role of CNSspecific T cells in CNS repair, our group has found that adaptive immune cells are key players in CNS maintenance under nonpathological conditions, especially in hippocampal plasticity. 9,14 We showed that autoreactive T cells are needed to support hippocampal-dependent learning and memory tasks, as well as for the regulation of adult hippocampal neurogenesis and neurotrophic factor production, 14 possibly by regulating microglial phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, although it is believed to underlie the pathogenesis of MS (13)(14)(15)(16), in other neurodegenerative processes including brain injury (17,18), amyotrophic lateral sclerosis (19), stroke (20), and Alzheimer's disease (AD), T cell infiltration into the CNS has been implicated either as exacerbating neurodegeneration (21)(22)(23) or, in other instances, as beneficial. Regulatory cytokine profiles of certain T cell subsets (24)(25)(26) or the ability of T cells to secrete neurotrophic factors (27,28) have been suggested as mechanisms underlying the beneficial effects of T cell infiltration into the CNS.…”
mentioning
confidence: 99%